Bourreaux et victimes ? La difficile identité collective des Allemands au prisme du cinéma germanophone - Brigitte Rigaux-Pirastru (Amnis)
West-Germany, then reunified Germany, accepted the judicial and moral heritage of the 3rd Reich; as such its identity built up on the memory of Nazi crimes, particularly the holocaust. The Germans themselves paid a heavy toll to the war of aggression, the flight and the expulsion of 14 millions of people, from Central and South-East Europe constitute one of the deadly consequences of this war. Through several successful German movies (from 1951 to 2015), we will study the memorial mutations of the flight and the expulsion on the screen – which are sometimes concurrent with those of the war and of the holocaust. Cinema, “agent of history” (Marc Ferro), indeed plays a major role as a witness or possibly even as an actor of these memorial evolutions, which are sometimes spectacular in a country characterised by a definitely unique history.